Social cues from neighboring patches influence patch dynamics in a spatially structured population of a colonial bird - Killian A. Gregory; Charlotte Francesiaz; Jean‐Yves Barnagaud; Pierre‐André Crochet; Jean‐Dominique Lebreton; Aurélien Besnard; Julien Papaïx (Ecology, 2026)
The dynamics of spatially structured populations (SSPs) depend on dispersal movements between habitat patches. Individual‐level studies show that dispersal can be informed by social cues about habitat quality, such as breeding success or the number of conspecifics in a patch. However, informed dispersal has rarely been considered in studies investigating SSP dynamics. In particular, little is known about how patch dynamics are influenced by characteristics of neighboring patches, and the spatial scale of this influence. Here, we used occupancy and growth rate models to investigate the effect of breeding success and numbers in all patches of an SSP of black‐headed gulls ( Chroicocephalus ridibundus ) on patch colonization, persistence and growth rates. The spatial scale of influence of neighboring patches was estimated using a distance decay function weighting the effect of patch covariates. Our results showed a strong influence of breeding success and breeding numbers, both in the focal patch and in neighboring patches, on patch dynamics. Persistence was higher for patches occupied by large and successful colonies, suggesting high attractiveness of such colonies, although their growth rate was reduced, probably due to increased costs of group‐living. Patch colonization rates were higher within a few kilometers from patches occupied by large and successful colonies, in accordance with an attraction of dispersers to areas showing favorable breeding conditions. The breeding success of neighboring patches from the entire SSP reduced patch persistence, but only for patches that failed to produce chicks, and negatively affected the growth rate of persisting colonies, consistent with individuals moving away towards higher quality habitats. These results advocate for the use of social information in black‐headed gull dispersal decisions. However, we were unable to distinguish between the use of breeding success (public information) and breeding numbers (conspecific attraction), which were highly correlated. Our findings emphasize the need to consider neighboring patches as dynamic components of the landscape that actively shape dispersal decisions, with consequences on SSP dynamics.

A multi‐population approach supports common patterns in marine growth and maturation decision in Atlantic salmon ( Salmo salar L.) from southern Europe - Cécile Tréhin; Etienne Rivot; Valentin Santanbien; Rémi Patin; Stephen D. Gregory; Ludivine Lamireau; Frédéric Marchand; William R. C. Beaumont; Luke J. Scott; Robert Hillman; Anne‐Laure Besnard; Pierre‐Yves Boisson; et al. (Journal of Fish Biology, 2024)
This study provides a regional picture of long‐term changes in Atlantic salmon growth at the southern edge of their distribution, using a multi‐population approach spanning 49 years and five populations. We provide empirical evidence of salmon life history being influenced by a combination of common signals in the marine environment and population‐specific signals. We identified an abrupt decline in growth from 1976 and a more recent decline after 2005. As these declines have also been recorded in northern European populations, our study significantly expands a pattern of declining marine growth to include southern European populations, thereby revealing a large‐scale synchrony in marine growth patterns for almost five decades. Growth increments during their sea sojourn were characterized by distinct temporal dynamics. At a coarse temporal resolution, growth during the first winter at sea seemed to gradually improve over the study period. However, the analysis of finer seasonal growth patterns revealed ecological bottlenecks of salmon life histories at sea in time and space. Our study reinforces existing evidence of an impact of early marine growth on maturation decision, with small‐sized individuals at the end of the first summer at sea being more likely to delay maturation. However, each population was characterized by a specific probabilistic maturation reaction norm, and a local component of growth at sea in which some populations have better growth in some years might further amplify differences in maturation rate. Differences between populations were smaller than those between sexes, suggesting that the sex‐specific growth threshold for maturation is a well‐conserved evolutionary phenomenon in salmon. Finally, our results illustrate that although most of the gain in length occurs during the first summer at sea, the temporal variability in body length at return is buffered against the decrease in post‐smolt growth conditions. The intricate combination of growth over successive seasons, and its interplay with the maturation decision, could be regulating body length by maintaining diversity in early growth trajectories, life histories, and the composition of salmon populations.

Breeding habitat selection across spatial scales: is grass always greener on the other side? - Paul Acker; Aurélien Besnard; Jean‐Yves Monnat; Emmanuelle Cam (Ecology, 2017)
Habitat selection theory predicts that natural selection should favor mechanisms allowing individuals to choose habitats associated with the highest fitness prospects. However, identifying sources of information on habitat quality that individuals use to choose their breeding habitat has proved to be difficult. It has also proven difficult to identify dispersal costs that prevent individuals from joining the highest‐quality sites. A synthesis that integrates dispersal costs and habitat selection mechanisms across space has remained elusive. Because costs of dispersal are generally distance‐dependent, we suggest that a habitat selection strategy of sequential proximity search ( SPS ) can be favored by natural selection. This strategy requires that animals make decisions at multiple scales: whether to stay or leave the previous breeding site, depending on reproductive success; then, if dispersal is chosen, use information on neighborhood habitat quality to decide whether to stay in the neighborhood or leave, expanding the search area until the nearest suitable site is chosen. SPS minimizes distance‐dependent dispersal costs while maximizing benefits of gaining a better habitat. We found evidence of breeding dispersal behavior consistent with this strategy in a kittiwake population stratified into a spatial hierarchy from colonies to nest sites. We used a mixed sequential regression model to study dispersal decisions, indexed by breeding dispersal movement, of 2,558 individuals over 32 yr. Scale‐dependent dispersal propensities of kittiwakes varied according to breeding status, breeding experience, sex and individual identity. We suggest that distance‐dependent dispersal costs result from strong competition among kittiwakes for nest sites. Individual decisions regarding dispersal (whether to leave or not, and where to go) depend on nesting habitat quality as well as the competitive ability required to keep territory ownership in a previous site, or to acquire a new site; this ability varies according to distance between sites and individual characteristics. Additional studies are needed to establish the generality of SPS in habitat selection.

Normo or hypobaric hypoxic tests: propositions for the determination of the individual susceptibility to altitude illnesses - Gustave Savourey; Jean-Claude Launay; Yves Besnard; Angélique Guinet-Lebreton; Antonia Alonso; Fabien Sauvet; Cyprien Bourrilhon (European Journal of Applied Physiology, 2007)

Control of erythropoiesis after high altitude acclimatization - Gustave Savourey; Jean-Claude Launay; Yves Besnard; Angélique Guinet; Cyprien Bourrilhon; Damien Cabane; Serge Martin; Jean-Pierre Caravel; Jean-Marc Péquignot; Jean-Marie Cottet-Emard (European Journal of Applied Physiology, 2004)

Sympathetic stimulation induced by hand cooling alters cold-induced vasodilatation in humans - Isabelle Sendowski; Gustave Savourey; Jean-Claude Launay; Yves Besnard; Jean-Marie Cottet-Emard; Jean-Marc Pequignot; Jacques Bittel (European Journal of Applied Physiology, 2000)

Positive end expiratory pressure as a method for preventing acute mountain sickness - Gustave Savourey; Richard Caterini; Jean-Claude Launay; Anglique Guinet; Yves Besnard; Anne-Marie Hanniquet; Jacques Bittel (European Journal of Applied Physiology, 1997)

Cold induced vasodilatation and cardiovascular responses in humans during cold water immersion of various upper limb areas - Isabelle Sendowski; Gustave Savourey; Yves Besnard; Jacques Bittel (European Journal of Applied Physiology, 1997)